Mathematical modeling of the process of the armored chlorine-copper stripe forming - E. F. Baranovskij; V. M. Iljushenko; V. A. Pumpur (Литьë и металлургия)
In the article there is described the mathematical model of the forming process of the armored chlorine copper belt at continuous casting into rolling crystallizer, and also given the appropriate packet of programs.